SINTESIS α-PINENE MENJADI α-TERPINEOL MENGGUNAKAN KATALIS H2SO4 DENGAN VARIASI SUHU REAKSI DAN VOLUME ETANOL - Elvianto Dwi Daryono (Jurnal Teknik Kimia USU, 2015)
This study is intended to explore the optimum temperature reaction and volume of ethanol in the synthesis of α-pinene to α-terpineol. Turpentine oils that is used in this study contains α-pinene by 79.05%. In this study the variables used is the reaction temperature (60º, 70º, and 80ºC) and the volume of ethanol (105, 115, 125, 135 and 145 mL). Synthesis is done during 4 hours using a three-neck flask, condenser, hot plate, a magnetic stirrer, and a thermometer with a stirring speed of scale 7(350-700 rpm). After that, the results is neutralized to pH 7 using NaOH 5% then it is diluted with ethanol in 250 mL volumetric flask. Synthesized samples were analyzed by Gas Chromatography method. In this study, the highest concentration of α-terpineol obtained 57.05% with yield 67,79% at temperature reaction 70oC and the volume of ethanol is 135 mL.